What does Violet see? : raindrops and puddles - Aigner-Clark, Julie; Zaidi, Nadeem (New York : Hyperion Books for Children, 2002)
Follows Violet the mouse as she explores the world outside after it rains, investigating such things as a puddle, a stone, and a leaf.
Cover title.
On board pages with one textured page.
2.3
K-3
K-3
Keywords: Mice -- Juvenile fiction; Rain and rainfall -- Juvenile fiction; Photography -- Juvenile fiction; Toy and movable books -- Specimens; Mice -- Fiction; Rain and rainfall -- Fiction; Photography -- Fiction; Toy and movable books; Rain -- Fiction; Photography -- Fiction; Toy and movable books